DESCRIPTION OF THE USE OF TRADITIONAL MEDICINE FOR SWAMEDICATION IN THE COMMUNITY OF BAYUNING VILLAGE, KADUGEDE DISTRICT, KUNINGAN REGENCY - Merita Kristianti; Fitri Zakiah; Siti Pandanwangi; Aldhi Bayu (Indonesian Journal of Multidisciplinary Science, 2022)
This study aims to describe the use of traditional medicine for self-medication in the community in Bayuning Kadugede Kuningan Village. The type of research conducted is non-experimental research on respondents who live in Bayuning Village with 35 respondents using a questionnaire. Sampling is done by quota sampling. Analysis of the use of traditional medicine for self-medication was carried out descriptively. The description of the use of traditional medicine in Bayuning Village is that traditional medicine is used in various dosage forms to treat minor ailments, degenerative diseases and some are used to treat infections. Most of the traditional medicines used do not cause side effects (81%), when side effects occur, some respondents stop traditional medicine, but some go to the doctor or switch to modern medicine. The dosage of use is based on personal experience or passed down from family and most of them do not know the dosage of using these traditional medicines